Testing the Dornbusch Overshooting Theorem in Malawi - Zulu, Chimwemwe; Dunga, Hannah (Acta Universitatis Danubius. Œconomica, 2022)
The overshooting theorem as pioneered by Rudiger Dornbusch has aided monetary policy conduct for many years. However empirical evidence on its validity is mixed. This paper re-examined the validity of the overshooting phenomenon using the autoregressive distributed lag (ARDL) bound test approach. To achieve the main object the paper firstly examined if the United States/Malawi Kwacha (USD-MWK) exchange rate overshoots or undershoots its long run exchange rate. In addition, the research paper tested if there exist any fundamental macroeconomic fluctuations (money supply, real gross domestic product (GDP), interest rates and inflation rates) that may alter the spot exchange rate in a theoretically derived price-flex model. The study used a forty-one-year span of yearly nominal (USD-MWK) exchange rate data and that of monetary fundamentals data from World Bank development indicators (WDI) and the National statistical office (NSO) Malawi. The other data for each country were sourced from the International Financial Statistics (IFS). All the exchange rate used was from the Reserve Bank of Malawi (RBM). The results indicated that empirically only the inflation rate differential is economically significant in triggering spot rate rapid movements in the Price-Flex model. Conclusively, exchange rate overshooting has tested to be evident in Malawi. Solely attributed by the significant inflation rate differential where the other fundamentals are not statistically significant at 5% level of significance. This has been due to the constrained workability of the specified Price-Flex mathematical model in our economic environment.